2004
DOI: 10.2460/javma.2004.224.79
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of radiation therapy for incompletely resected grade-III mast cell tumors in dogs: 31 cases (1987–1998)

Abstract: Without further treatment, incompletely excised grade-III mast cell tumors have high local-regional recurrence; local-regional treatment with radiation may effectively be used to manage many such tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 24 publications
8
69
2
2
Order By: Relevance
“…A recent report by Hahn et al described a positive outcome in dogs with high-grade MCT treated with RT alone. Of note, all of these dogs received PNI [13]. The results this group obtained are significantly different than those reported by others employing surgery [2,3,20,22,25].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A recent report by Hahn et al described a positive outcome in dogs with high-grade MCT treated with RT alone. Of note, all of these dogs received PNI [13]. The results this group obtained are significantly different than those reported by others employing surgery [2,3,20,22,25].…”
Section: Discussioncontrasting
confidence: 53%
“…To our knowledge, this is the first study that has demonstrated a statistical association between mucous membrane origin and outcome in canine MCT. Some studies have identified tumour size as a prognostic factor in canine MCT [13,19]. Unfortunately, the majority of patients identified in this study underwent surgery prior to referral, and tumour size was thus often impossible to determine retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, local recurrence rates for MCT range from 10 to 50% in the literature 2,3,25‐27 . However, status of the surgical margins was not known in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many dogs develop MCTs on distal limbs or on the head in sites where complete surgical excision cannot be achieved with preservation of the limb or the anatomy of the area. Post‐operative radiotherapy appears to increase the survival time of solitary grade II and grade III MCTs following incomplete surgical excision (Al‐Sarraf et al ., 1996; Frimberger et al ., 1997; Hahn et al ., 2004). In some cases, the diffuse and/or extensive nature of the tumour mass precludes even cytoreductive surgery, and these cases are often referred for radiotherapy.…”
Section: Introductionmentioning
confidence: 99%